2015
DOI: 10.5815/ijigsp.2015.08.06
|View full text |Cite
|
Sign up to set email alerts
|

Dual Transition Uniform Lbp Matrix for Efficient Image Retrieval

Abstract: Texture image retrieval plays a significant and important role in these days, especially in the era of bigdata. The big-data is mainly represented by unstructured data like images, videos and messages etc. Efficient methods of image retrieval that reduces the complexity of the existing methods is need for the big-data era. The present paper proposes a new method of texture retrieval based on local binary pattern (LBP) approach. One of the main disadvantages of LBP is, it generates 256 different patterns on a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Recently the color texture analysis methods that integrate the color components with textural features have attracted significant attention [25,26,27]. The researchers' pachos [28] conducted the investigation on the role of color attributes in texture classification and they have experimented on 50 images using HSV, LAB and RGB color models and found that HSV color space is the best when compared to the other. The local binary pattern (LBP) [29] and Gabor filter descriptors are used with different color spaces using both parallel and integrative approaches on Outex-13, Outex-14 and MIT-VisTex color databases.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Recently the color texture analysis methods that integrate the color components with textural features have attracted significant attention [25,26,27]. The researchers' pachos [28] conducted the investigation on the role of color attributes in texture classification and they have experimented on 50 images using HSV, LAB and RGB color models and found that HSV color space is the best when compared to the other. The local binary pattern (LBP) [29] and Gabor filter descriptors are used with different color spaces using both parallel and integrative approaches on Outex-13, Outex-14 and MIT-VisTex color databases.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Uniform LBP is treated as the fundamental properties of texture image, and there is 80% to 85% of the texture images contain only Uniform LBP. 15) The number of uniform LBP patterns is P (P-1) + 2, P is the number of pixels in the field. For 8…”
Section: Uniform Lbpmentioning
confidence: 99%
“…Texture plays an important role in image classification, retrieval, segmentation and age classification. In Literature various texture based methods are derived for image classification [ 15,16,17], face recognition [18,19,20], age and facial expressions identification [21,22], segmentation [23,24,25] image retrieval [26,27,28,29,30,31,32 ]. Texture is salient and indispensable feature for CBIR.…”
Section: Introductionmentioning
confidence: 99%